Beyond Evaluation: Cultural Reflexivity and Pedagogical Identity in Metaevaluating Pre-Service Teacher Planning - Rivera, Judith Jaqueline Maldonado (Journal of Posthumanism, 2025)
In the metaevaluation of lesson planning in pre-service teacher education, this study puts planning on the line as a pedagogical act that is indicative of the epistemological stances and ethical commitments of a teacher. Leverag-ing 947 genuine lesson plans as dataset, the study is designed in a methodo-logical nature which is a combination of descriptive analysis and advanced statistics modeling. A 14-item rubric (based on national standards and evalu-ative theory) was employed to evaluate the coherence, inclusiveness, and methodological quality of the plans. Descriptive findings indicated con-sistent strengths in the objective clarity category and consistent weaknesses across the categories of curriculum adaptation and impact evaluation. The study uncovered latent cognitive patterns and three types of emerging plan-ning activities (i.e., strategically coherent, pedagogically fragile, transitional) through Principal Component Analysis (PCA) and K-Means clustering. By recognizing lesson planning as an act shaped by sociocultural identity, ethi-cal reasoning, and epistemic diversity, this research situates metaevaluation within broader cultural and pedagogical ecologies. These results fill crucial gaps in the literature in the form of a data-grounded, typological model of formative assessment, and pave the ways for new AI-guided feedback sys-tems. The study reconceptualizes metaevaluation to be a critical reflexive process and a site for transformative learning, contributing to broadening theoretical concepts as well as practical tools for teacher education.